A molecular dynamics study of heterogeneous nucleation in generic liquid/substrate systems with positive lattice misfit. (2nd December 2020) - Fan, Z; Men, H
Abstract: Nucleation plays a critical role in many natural and technological processes, and nucleation control requires detailed understanding of nucleation process at atomic level. In this study, we investigate the atomistic mechanism of heterogeneous nucleation in generic systems of liquid/substrate with positive lattice misfit (the solid has larger atomic spacing than the substrate) using molecular dynamics (MD) simulations. We found that heterogeneous nucleation process in such systems can be best described by a 3-layer nucleation mechanism: formation of the completely ordered first layer with an epitaxial relationship with the top surface of the substrate; formation of vacancies in the second layer to accommodate lattice misfit; and creation of a nearly perfect crystal plane of the solid in the third layer that demarcates the end of nucleation and the start of crystal growth. This 3-layer nucleation process creates a 2D nucleus (a plane of the solid phase), which contrasts with the hemisphere of the solid (a 3D nucleus) in the classical nucleation theory (CNT). It is expected that this 3-layer nucleation mechanism will provide new insight for nucleation control through effective manipulation of the liquid/substrate interface.